تأثير الإصابة بسوسة الهالوك Smicronyx cyaneus Gyll. وذبابة الهالوك Phytomyza orobanchia Kalt. في بعض مؤشرات نمو الهالوك المتفرع Orobanche ramosa L. في حقول البندورة - أحمد, محمد; الرهبان, بهاء; حبق, حنان (Latakia University Journal -Biological Sciences Series, 2016)
درس تأثير تغذية يرقات ذبابة الهالوك Kalt. Phytomyza orobanchia وسوسة الهالوك .Gyll cyaneus Smicronyx، ضمن أفرع بذور الهالوك المتفرع وكبسولاته Orobanche ramosa L. ، الذي يصيب البندورة في بعض مؤشرات نموه ، وهي: طول الفرع ، عدد الكبسولات /الفرع، الوزن الرطب والجاف للفرع. أشارت النتائج إلى فعالية هذه التغذية في خفض الكتلة الحيوية للهالوك، إذ سببت خفضاً في قيم جميع مؤشرات نمو نباتات الهالوك المتفرع المصابة مقارنة مع السليمة ، وبفروق معنوية، بينما سببت الإصابة المختلطة بيرقات النوعين معاً خفضاً أكبر في قيم هذه المؤشرات ، وبفروق معنوية عالية نسبةً لكل من طول الفرع ، عدد الكبسولات /الفرع ، والوزن الرطب للفرع المصاب مقارنة مع السليم. بلغ معدل الانخفاض الناتج عن الإصابة المختلطة إلى 57.2%، 76.7%، 58.8%، 55.5% لكل من طول الفرع، عدد الكبسولات /الفرع ، الوزن الرطب والوزن الجاف على التوالي. تشير النتائج إلى الدور الممكن لسوسة الهالوك و ذبابة الهالوك في خفض كثافة الهالوك المتفرع في حقول البندورة على الساحل السوري. The impact of larvae feeding of of the agromyzid fly (Phytomyza orobanchia Kalt., and curculionid weevil (Smicronyx cyaneus Gyll.), inside shoots and seed capsules of branched broomrape (Orobanche ramosa L.) which infested tomato, in some phenological parameters: shoot length, number capsules/shoot, wet and dry weight of shoot, were determined. The results indicate to the efficacy of larvae feeding in reduction of O. ramosa bio-mass, it caused significant reduction in the values of all studied parameters, of infested branched broomrape plants in comparison to healthy ones, While the mixed infestation of the both insects caused higher reduction in the values of these parameters, with high significant differences in: shoot length, number capsules/ shoot, and wet weight of infested shoot, in comparison with healthy ones. the reduction rate which resulted from mixed infestation reached to 55.5%, 58.8%, 76.7%, 57.2% for shoot length, number capsules/ shoot, wet weight and dry weigh respectively. The results indicate to the potential role of P. orobanchia and S. cyaneus in reduction the density of O. ramosa in tomato fields, at the Syrian coastal region.